2022
DOI: 10.1111/add.15811
|View full text |Cite
|
Sign up to set email alerts
|

Set‐up of a population‐based model to verify alcohol abstinence via monitoring of the direct alcohol marker phosphatidylethanol 16:0/18:1

Abstract: Background and aims Phosphatidylethanol 16:0/18:1 (PEth) is a biomarker for alcohol intake. It has a half‐life of 7.9 days. Chronic alcohol consumption causes high PEth values. It can take weeks before PEth values fall below the decision limit for ‘alcohol abstinence’. Our aim was to validate whether alcohol abstinence can be determined based on two consecutive PEth results above the decision limit. Design Observational study. Setting Belgium, February 2019. The study was linked to a social initiative in Belgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…This paved the way for PEth analysis using microsampling in combination with drying of the blood. Thereby, small volumes of capillary blood (typically 10–20 μl) are collected and allowed to dry on an absorbent sample support (e.g., cellulose filter paper or polymer‐based tips; Luginbühl, Weinmann, et al, 2019; Van Uytfanghe et al, 2021). PEth concentrations of samples collected using this technique were shown to be comparable between liquid whole blood samples, venous dried blood, and capillary dried blood (Kummer, Ingels, et al, 2016; Kummer, Lambert, et al, 2016; Luginbühl, Weinmann, et al, 2019).…”
Section: Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paved the way for PEth analysis using microsampling in combination with drying of the blood. Thereby, small volumes of capillary blood (typically 10–20 μl) are collected and allowed to dry on an absorbent sample support (e.g., cellulose filter paper or polymer‐based tips; Luginbühl, Weinmann, et al, 2019; Van Uytfanghe et al, 2021). PEth concentrations of samples collected using this technique were shown to be comparable between liquid whole blood samples, venous dried blood, and capillary dried blood (Kummer, Ingels, et al, 2016; Kummer, Lambert, et al, 2016; Luginbühl, Weinmann, et al, 2019).…”
Section: Evolutionmentioning
confidence: 99%
“…This is because changes in drinking behavior can be detected earlier and more accurately with PEth and also short‐term follow‐up is possible. Thereby, PEth can help to improve the diagnostic information and is, therefore, a valuable alcohol biomarker for driving aptitude assessments (Kummer, Wille, et al, 2016; Schröck et al, 2016; Van Uytfanghe et al, 2021). This is especially relevant, given the fact that in several assessment schemes individuals are only invited a limited number of days per year (e.g., 1–3) to provide a sample.…”
Section: Applicationsmentioning
confidence: 99%
“…PEth is a relatively new biomarker for detecting and grossly quantifying a person's use of alcohol. It provides high diagnostic sensitivity and specificity (lack of false positives-as known so far-also makes it suitable for verifying abstinence claims), slow degradation rate (mean half-life ranging from 3 to 10 days), strong correlation with the amount of alcohol consumed in the past 1-2 weeks (in individuals with AUD) and absence of gender and liver-disease biases (Arnts et al, 2021;Hahn et al, 2016;Helander et al, 2019;Van Uytfanghe, Heughebaert, et al, 2022). Technological and methodological advances (in particular the use of dried blood microsamples, such as DBS) have significantly reduced the complexity and costs of the preanalytical and analytical procedures associated with PEth determination (Biondi et al, 2019).…”
Section: Phosphatidylethanolmentioning
confidence: 99%
“…As PEth concentrations decrease as a function of abstinence length, PEth sensitivity is as low as 67% after 14 days of abstinence and 43% after 28 days of abstinence (Moore et al, 2018). Nevertheless, it has been shown that, based on the expected degradation of PEth, evaluation of abstinence is possible, even when two consecutive PEth results are still above the threshold for abstinence (McDonell et al, 2017; Van Uytfanghe, Heughebaert, et al, 2022), While blood PEth levels seem not to be influenced by age, sex, kidney diseases, or drug intake (Andresen‐Streichert et al, 2017), a more recent study, however, suggests that sensitivity is reduced for persons with, for example, anemia or a high BMI (Hahn et al, 2021).…”
Section: Direct Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation